Association Between Occupational Exposure to Formaldehyde and Cognitive Impairment. (8th February 2022) - Letellier, Noemie; Gutierrez, Laure-Anne; Pilorget, Corinne; Artaud, Fanny; Descatha, Alexis; Ozguler, Anna; Goldberg, Marcel; Zins, Marie; Elbaz, Alexis; Berr, Claudine
Abstract : Background and Objectives: To our knowledge, no study has investigated the effect of exposure to formaldehyde on cognition in the general population. Our objective was to examine the association between occupational exposure to formaldehyde and cognitive impairment in middle-aged and young-old adults (≥45 years). Methods: In the French CONSTANCES cohort, cognitive function was assessed with a standardized battery of 7 cognitive tests to evaluate global cognitive function, episodic verbal memory, language abilities, and executive functions (e.g., Digit Symbol Substitution Test [DSST]). A global cognitive score was created using principal component analysis. Cognitive impairment was assessed in reference to norms of neuropsychological battery according to age, sex, and education. Lifetime exposure to formaldehyde was assessed using a French Job Exposure Matrix created in the framework of the Matgéné project. After performing multiple imputation, separate modified Poisson regression models were used to evaluate the association between cognitive impairment (<25th percentile) and formaldehyde exposure (exposed/never exposed), exposure duration, cumulative exposure index (CEI), and combination of CEI and time of last exposure. Results: Among 75, 322 participants (median age 57.5 years, 53% women), 8% were exposed to formaldehyde during their professional life. These participants were at higher risk of global cognitive impairment (for global cognitive score: adjusted relative risk [aRR] 1.17; 95% confidence interval [CI] 1.11–1.23), after adjusting for confounders (age, sex, education, income, solvent exposure, Effort–Reward Imbalance, night shift, repetitive work, and noisy work). They were at higher risk of cognitive impairment for all cognitive domains explored. Longer exposure duration and high CEI were associated with cognitive impairment, with a dose–effect relationship for exposure duration. Recent exposure was associated with impairment in all cognitive domains. Time did not fully attenuate formaldehyde-associated cognitive deficits especially in highly exposed individuals (for DSST: high past exposure aRR 1.23; 95% CI 1.11–1.36; high recent exposure: aRR 1.24; 95% CI 1.13–1.35). Discussion: Our findings highlight the long-term detrimental effect of formaldehyde exposure on cognitive health in a relatively young population.